STUDI AKTIVITAS DAN MEKANISME ANTIKANKER IN VITRO EKSTRAK METANOLIK DAUN Dianella nemorosa Lam. (LILIACEAE) - KARIM, ADITYA KRISHAR; Asmara, Widya ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Plants have been important sources of compounds for the control and cure of many diseases including cancer.Dianella nemorosa Lam. also known as Tegari (Pra kepey) belonging to the Liliaceae family. This plant has been utilized for traditional medicine by local community in Papua. The aims of the research was to identifies group of compounds in D. nemorosaleaves methanolic extract, to find out the cytotoxic activity of this extract against selected human cell line, and to analyze induction of p53 protein expresssion as well as inhibition of COX-2 protein expression onthe most selective cancer cell line. Methanolic extract was obtained by extracting the leaves powder using methanol. Extract was then applied into human cell line namely human breast carcinoma cell line (MCF-7 & T47D), colon carcinoma cell line (WiDR), human Ã-lymphoma cell line (Raji cell) and cervical cancer cell line (HeLa) using MTT (3-(4,5-dimetilthiazol-2-il)-2,5-difenil tetrazolium bromida) assay, and for adherent mouse myoblast cell line (C2C12), human kidney cell line (293A), colorectal cell line (HCT-116), cervical cancer cell line (HeLa) and gastric cell line (MKN 45) using WST-1 (2-(4-iodophenyl)-3-(4-nitro-phenyl)-5-(2,4-disulfo phenyl)-2H-tetrazolium monosodium salt) assay. The plant was identified by Botany Laboratorius-Herbarium, Indonesian Institute of Science (LIPI) and Plant Taxonomy Laboratorius, Gadjah Mada University, whereas identification of compounds groups was done using thin layer chromatography (TLC). Identification of the induction of p53 protein and suppression of COX-2 protein expression was assayed by immunocytochemical methods. This result indicated that the methanolic extract of D. nemorosaleaves possessed selectively cytotoxic activities against HeLa cell line with IC50values of 593.62 Âµg/ml compare with MCF7, T47D, WiDR and Raji cell lines with IC50values of 1.744 Âµg/mL, 1.390 Âµg/mL, 1.865 Âµg/mL and 1.779 Âµg/mL, respectively, after incubated for 24 h using MTT assay. The methanolic extract of D. nemorosa leaves also exhibited selectively cytotoxic activities against HeLa and HCT-116 with IC50values of 233.95 Âµg/mL and 199.31 Âµg/mL, repectively compare to C2C12 (IC50values of 405.51 Âµg/mL) and 293A (IC50values of 580.81 Âµg/mL), but had no cytotoxic against MKN45 cell line (IC50> 500 Âµg/mL) after incubated for 72 h using WST-1. Methanolic extract of D. nemorosa leaves can induce p53 protein expression but not suppress of COX-2 protein expresssion in HeLa and HCT-116 cell line. It was concluded that methanolic extract of D. nemorosaleaves possesses inhibitory effect on cell growth (cell cycle arrest) in HeLa and HCT-116 cell line by inducing of p53 protein.